The Human side of Information Systems: capitalizing on People, as a basis for Organization Development and Holistic Change - Henriques, T.; O'Neill, Henrique (Handbook of Research on Innovations in Information Retrieval, Analysis, and Management, 2015)
In this chapter the authors explore the relationship between Information Systems and Organization Development, highlighting the value that Holistic Change Interventions can introduce when applied to IS/IT areas, mobilizing Individuals, Groups and the whole Organization to promote Organizational Effectiveness. A “soft” approach to Organizational Change is proposed, focusing on main internal aspects which are determinant for Organizational Performance, including Organizational Culture and Values, Leadership, Work Teams, and Employee Engagement. The approach is illustrated by a successful “real-world” Transformational Change Program which has been developed, within an IT Unit of a major financial organization, following an Action Research paradigm. The intervention has integrated two main cycles – a first one covering the strategy determination and behavioral preparation for further action, and a second one devoted to a coordinated implementation of strategic actions which have emerged from the first cycle – where communication, engagement, action and improvement have been the most relevant attributes of the whole process. From a Research perspective this successful Change intervention has served to develop and test, within context, a Framework of Critical Success Factors for Holistic Change, which is described on its management implications, and covering distinct areas and dimensions. Also, the high potential of Action Research, to promote Holistic Change within real organizational settings, and, simultaneously, to address complex research issues, questions, objectives, and test hypothesis, is deeply illustrated within this chapter.